Evidence of a Role for the TRPC Subfamily in Mediating Oxidative Stress in Parkinson’s Disease - Maria-Ferreira, Daniele; de Oliveira, Natalia Mulinari Turin; da Silva, Liziane Cristine Malaquias; Fernandes, Elizabeth Soares (Frontiers in Physiology, 2020)
Parkinson’s disease (PD) represents one of the most common multifactorial neurodegenerative disorders of the elderly population. It is associated with aggregation of α-synuclein protein and loss of dopaminergic neurones in the substantia nigra pars compacta of the brain. The disease is mainly represented by motor symptoms that develop slowly over time and includes, for instance, resting tremor, postural instability, rigidity, and bradykinesia, besides disturbance in non-motor functions. Although the pathology of PD has not been yet fully understood, it has been suggested that the disruption of the cellular redox status may contribute to cellular oxidative stress and thus, to cell death. The generation of reactive oxygen species and reactive nitrogen intermediates and dysfunction of dopamine metabolism play important roles in the degeneration of dopaminergic neurones. In this context, the transient receptor potential channel canonical (TRPC) sub-family plays an important role in neuronal degeneration. Additionally, PD gene products, including DJ-1, SNCA, UCH-L1, PINK-1 and parkin also interfere with mitochondrial function leading to reactive oxygen species production and dopaminergic neuronal vulnerability to oxidative stress. Herein, we discuss the interplay between these various biochemical and molecular events which ultimate lead to dopaminergic signalling disruption, highlighting the recent identified roles of TRPC in PD.